TRAINING OF MASTERS OF PUBLIC MANAGEMENT AND ADMINISTRATION: ISSUES OF RAISING EFFICIENCY - Bulba V.Н.; Postupna O.V. (Pressing Problems of Public Administration, 2016)
In the article on the basis of theoretical and practical experience are considered promising directions of increase of ef ciency of scienti c-educational activity of training educational level “master” specialty 074 “Public Management and administration  eld of knowledge management and 07 “administration”.